2011
DOI: 10.1177/230949901101900114
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Total Knee Arthroplasty for Valgus Knees: Soft-Tissue Release Technique and Implant Selection

Abstract: Adequate lateral soft-tissue release is the key to successful TKAs in valgus knees. The choice of implant depends on the severity of the valgus deformity and the extent of soft-tissue release needed to obtain a stable, balanced flexion and extension gap, in order to achieve minimal constraint with maximum stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…7 In the study of Lu et al, out of 74 patients 63 were women and 11 were men with mean age of 62.93 years. 8 Both observations in our study, mean age and female preponderance, were found to be consistent with Elkus et al study and Lu study.…”
Section: Incidence With Age and Sexsupporting
confidence: 93%
See 1 more Smart Citation
“…7 In the study of Lu et al, out of 74 patients 63 were women and 11 were men with mean age of 62.93 years. 8 Both observations in our study, mean age and female preponderance, were found to be consistent with Elkus et al study and Lu study.…”
Section: Incidence With Age and Sexsupporting
confidence: 93%
“…8 All knees had a good patellar position and were clinically stable in both mediolateral and anteroposterior planes. No radiolucency was noted.…”
Section: Valgus Anglementioning
confidence: 90%
“…In the knees with valgus deformity, release of the iliotibial band was performed via pie-crusting with a needle [6,7,44]. If required, additional release of the lateral collateral ligament, popliteus tendon and posterolateral capsule was carried out with great care, as there is a risk of posterolateral flexion gap instability, which necessitates the use of a constrained condylar prosthesis design [12,27,43,56]. Ligament balancing was performed with the trial implants in place.…”
Section: Surgical Techniquementioning
confidence: 99%
“…There is evidence that surgery in patients with a worse condition is less likely to be successful, particularly with valgus deformity progressing beyond 25° 33. It is important to monitor all patients attending such clinics specifically for valgus deformity and for overall function for example with the Oxford Knee Score 34…”
Section: Discussionmentioning
confidence: 99%